Usability Evaluation in Electronic Employee Performance Reports Using the Usability Testing Method - Elsy Rahajeng (Universitas Syiah Kuala, 2021)
Employee Performance Reports electronically (LKP) are used by lecturers to periodically report performance on performance for 6 months which includes teaching, research, and community service plus support. Sometimes in the reporting, there are obstacles experienced by lecturers related to filling out the report. The purpose of this research is to measure effectiveness, efficiency, and user satisfaction. Besides that, I want to know the topics that are often discussed by the lecturer participants. This research was conducted involving 5 lecturers who actively used E-LKP. Data collection was carried out through experiments in which participants used E-LKP and gave their opinions about E-LKP using the Think Aloud method and analyzed using QDA Miner Lite. This usability testing test results show that the effectiveness value is 95%, the efficiency value is 96% and the SUS value is 61. The results of think-aloud when working on assigned scenarios are analyzed using QDA Miner Lite software so that the 6 highest coding frequencies in this study are Activity, Assignment Letters, External Activities, Moving Activities, Activity Codes, and Research.